THE ROLE OF INNOVATIVE TRANSLATION EDUCATION IN DEVELOPING TRANSLATION SKILLS AMONG IRAQI STUDENTS - Sadeq Adil Ali Altameemi (Scholars Digest Publishing, 2025)
In order to have a strong system in the field of higher education and to achieve its goals and missions, teaching and training methods play a very important role. Given the rapid and complex changes in the world, education must also be updated and creative and innovative methods must be used to achieve better results. In recent years, the Covid-19 pandemic has revealed this issue more than ever and has severely affected the education system. Teaching translation as one of the problematic topics for foreign teachers and students is not far from this issue. In this article, the author has tried; with an analytical-descriptive method and relying on library studies and field observations of reputable universities and translation centers, to address the significant impact that the use of creative and innovative methods in teaching can have on the development of translation skills among students. For better results, we have considered Iraqi students as an example and at the end, solutions in this field have been presented. It is expected that the results of this study can help decision-makers and policymakers in the field of higher education and important centers such as the Ministry of Foreign Affairs to develop and promote innovation in this field and improve the quality of teaching and learning and the labor market in the field of translation.
Keywords: Higher education, teaching translation, innovation, translation skills, creative education, Iraqi students.